Food culture and health in pre-modern Islamic societies - Waines, David. (EI Reference Guides, 2011)
This book brings together edited articles from the second edition of the Encyclopaedia of Islam that are relevant to food culture, health, diet, and medicine in pre-Islamic Muslim societies. This compilation consists of edited entries on agriculture and irrigation, with attention for various staples and fruits; animals and the legal aspects of their consumption; hunting and fishing; the preparation of food, with entries on both the kitchen and various ingredients; dietetics and pharmacology; and the medicinal properties of a wide variety of foodstuffs.